Partial Molar Pregnancy Presenting as a Tubal Ectopic Pregnancy - Mariam Ayyash; Monica Kole; Quoc Le; Yulei Shen; Monique Swain (Hindawi Limited, 2022)
Background. Tubal molar pregnancy is extremely rare, with no more than 200 cases reported in the literature. The incidence is approximated at 1.5 per 1,000,000 pregnancies. Case. We report the case of a 22-year-old woman with an overall initial stable clinical presentation who was noted to have a ruptured ectopic pregnancy. She was surgically treated, and pathology revealed partial hydatidiform molar ectopic pregnancy. At the time of surgical intervention, the treating physicians had not considered molar ectopic pregnancy within the differential diagnosis, since this is a very rare presentation. Once the pathology was discovered, the patient was contacted to be scheduled for close follow-up and counseling to reduce progression to choriocarcinomas. Conclusion. This case report highlights the importance of sending, reviewing, and following up on pathologic specimens for all patients undergoing surgical intervention for presumed ectopic pregnancy and ensuring that appropriate follow-up is in place for those patients.